Modelling cross-border transport: Three cases in Öresund - Tom Petersen (European Regional Science Association (ERSA), 2004)
Transport models, and transport/land-use interaction models, are important decision support tools for large-scale infrastructure investments, for example in the road network. A bothersome feature of these tools are their distant forecasting horizon of 10–30 years ahead, and the uncertainty following from this. Although widely used, these models have rarely been put to test after this period have passed. The predictive power of a transport model is dependent on its ability to reproduce reality, which is assessed by validation. Apart from modelling the specific transport demand, which is based partly on socio-economic (demand) factors and partly on the supply of transport facilities (infrastructure), a number of scenarios of the future socio-economic development must be set up, called the scenario assumptions. In this paper we will present three different transport models: FREDRIK/ SSV, COMVIN and SAMPERS/ Skåne, out of which the first two have been used to model the transport across the Öresund Strait. The model structure, forecast results and scenario assumptions are considered in order to identify the key sources of uncertainties, and to prepare for the estimation of the true model error versus the error caused by incorrect scenario assumptions. Key words: infrastructure planning, transport models, validation, Öresund, before-and-after data.
Keywords: 330; infrastructure planning; transport models; validation; Öresund; before-and-after data